East Asian financial integration: a cointegration test allowing for structural break and the role of regional institutions - Ibrahim, Saifuzzaman (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
This study investigates the progress of ASEAN+3 financial markets integration after the 1997 Asian financial crisis. Adopting a Gregory and Hansen (1996) cointegration test that takes into account structural break of the series, this study finds no significant improvement in the intraregional financial market integration after the crisis. This may imply that measures that were introduced and implemented in the aftermath of the 1997 crisis may have not effectively affect the region’s financial market integration. Several factors attribute to this including the differences in the ASEAN+3’s institutional and legal frameworks.